(3bdGFO GddLjf Ydi fMh QbQI GdYjfs - (3HGfe Hf Me NJGQ GdMGLjs ((3JTjJ(B_ (3ehQjJGfjG s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd cJGHg GdeHjf hHYO aNjQ GdYdhe hCYdGgG QJHg Yde CUhd GdOjf hGdTQGFY hbO cGf TjNfG gh hGdOfG GdEeGe LeY LedI eNJUQI LGdHI ef Ld GdCHhGH CgegG SeGgG (B: (3bQI GdYjf hERGdI GdTchc hGdQjHI s
(3BNQgG (B:s
(3hQhi eSde Yf CHj SYjO GdNOQi Yf GdfHi bGd (B: (3EPG ONd Cgd GdLfI GdLfI SLGA HGdehJ cCfg cHT CedM Ke bQC QShd Gddg hCfPQge jhe GdMSQI bO EfbVi eG CQOfG LeYg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdESdGejs